The Influence of Compilation and Evaluation of Key Performance Indicators (IKU) on the Quality of Performance Planning and Its Implications for the Value of Government Agency Performance Accountability (AKIP) - Handaningrum, Oktiva (Dinasti Publisher, 2025)
This study aims to analyze the influence of the compilation and evaluation of Key Performance Indicators (KPI) on the quality of performance planning and its implications for the value of Government Agency Performance Accountability (AKIP). KPIs are strategic tools used to measure the achievement of organizational objectives in a structured and measurable way. In practice, poorly designed KPIs that fail to meet SMART principles often result in inaccurate performance measurements and misalignment between institutional and individual indicators. This study adopts a literature review approach by analyzing relevant theories and empirical findings from various credible sources. The results indicate that relevant and periodically evaluated KPIs significantly improve performance planning quality and positively affect AKIP scores. Data-driven, participatory, and results-oriented planning directly contributes to government agencies’ performance accountability and transparency.